Segmentation Algorithm of Spine CT Image Based on Hidden Markov Ｒandom Field - LIU Xia; KUANG Ｒui-xue; WANG Bo; YUE Yu-ting (Journal of Harbin University of Science and Technology)
With little consideration about spatial information of pixels， most of the traditional image segmentation algorithms are not ideal. To this end，for the segmentation of spine CT images，an improved algorithm based on Hidden Markov random field framework has been proposed in this paper. The prior distribution of classification is established by Hidden Markov random field，and then we combine the Expectation-maximization based on Simulated Annealing with memory and the Maximum a posteriori estimation criterion to estimate parameters. The experimental results show that the algorithm in this paper has a great improvement on the accuracy of the segmentation of the spine.